COMPETENCY-ORIENTED APPROACH IN THE ASSESSMENT SYSTEMS OF GERMANY AND UZBEKISTAN - Zuhra Najmiddinova; Abdullayeva Zarina Dilshodbekovna (TADQIQOTLAR, 2025)
The evolution of competency-oriented evaluation in the educational systems of Uzbekistan and Germany is covered in this article. The competency-based approach emphasizes students’ capacity for independent thought, problem-solving, and application of information in real-world contexts. Germany is renowned for its robust dual education system, which combines classroom instruction with job training. By implementing criteria-based evaluation, bringing national standards into line with international frameworks, and enhancing teacher preparation, Uzbekistan is now upgrading its assessment system. The two systems are contrasted in the article, along with their advantages, disadvantages, and potential future developments. Additionally, it demonstrates how competency-oriented assessment helps students achieve better learning outcomes and get ready for the demands of the modern workplace.